The Influence of Video Media Counseling on Knowledge and Attitudes About Marriage in Adolescents at SMA N 1 Doro, Pekalongan Regency - Ika Hidayatul Ulya; Noveri Aisyaroh; Kartika Adyani (Universitas Nahdlatul Ulama Surabaya, 2023)
Early marriage is a phenomenon that appears among teenagers. Cases of early marriage are caused by external factors, namely socio-cultural, environmental, inappropriate media sources and lack of exposure to information about early marriage. One way to increase teenagers' knowledge and attitudes about early marriage is by providing health education through video media. The purpose of this study is to determine the effect of video media counseling on teenagers' knowledge and attitudes about early marriage at SMA N 1 Doro, Pekalongan Regency. The type of research used is pre-experimental one group pre-test and post-test design. The sample for this research was 76 respondents from class. This research obtained an average knowledge before 12.9 and after 28.3. The results of increasing knowledge before and after were 15.4 while attitudes were 12.6. The results of the Wilcoxon test obtained p value = 0.000 < 0.05 which shows that there is an influence before and after being given counseling using video media about early marriage to teenagers at SMA N 1 Doro, Pekalongan Regency. Conclusion: It is hoped that related institutions, academics, and researchers can use video media as reference material in providing education about early marriage. To increase the knowledge and attitudes of teenagers to avoid getting married at an early age.